Comparison of Cyclosporin A with Mitomycin C and gamma irradiation as inactivators of stimulator cells in the one-way mixed lymphocyte reaction - Anderson, Ronald (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2009.